HCV-RELATED VASCULITIS - Shafiq, Ahmad Joya; Gauhar, Kurmanova; Kurmanova, Kulyash; Sadykova , Assel D.; Bosatbekov, Erkebulan N. (Interdisciplinary Approaches to Medicine, 2021)
Up to 3% of people in the world are infected with HCV, and 75-80% of them have chronic currency of infection. In the clinical picture of HCV infection, a significant place is given to extrahepatic manifestations - more than half of patients suffer from lesions of the skin, kidneys, heart, blood vessels, autoimmune and lymphoproliferative syndromes associated with HCV. Usually, mortality from chronic hepatitis C is associated with liver cirrhosis and hepatocellular carcinoma, but in fact, more patients die from complications associated with the development of cryoglobulinemic vasculitis - chronic renal failure and cardiovascular catastrophes. 40-60% of patients with chronic HCV infection suffer from cryoglobulinemic vasculitis in a wide range of clinical manifestations: from minimal to life-threatening. The pathogenesis of mixed cryoglobulinemia syndrome is based on polyclonal activation of lymphocytes.The systemic nature of the lesion, which is observed in HCV infection, reflects its generalized nature with the involvement of many organs and tissues in the pathological process, which complicates timely diagnosis and treatment. A variety of systemic extrahepatic pathology, which often outstrips the clinical picture of hepatitis itself, masquerading as another disease means that a specialist of any profile can meet with chronic HCV infection and its consequences.